Evaluation of mechanical, physical, and morphological properties of epoxy composites reinforced with different date palm fillers - Alshammari, Basheer A.; Saba, Naheed; Alotaibi, Majed D.; Alotibi, Mohammed F.; Jawaid, Mohammad; Alothman, Othman Y. (MDPI, 2019)
The present study deals with the fabrication of epoxy composites reinforced with 50 wt% of date palm leaf sheath (G), palm tree trunk (L), fruit bunch stalk (AA), and leaf stalk (A) as filler by the hand lay-up technique. The developed composites were characterized and compared in terms of mechanical, physical and morphological properties. Mechanical tests revealed that the addition of AA improves tensile (20.60–40.12 MPa), impact strength (45.71–99.45 J/m), flexural strength (32.11–110.16 MPa) and density (1.13–1.90 g/cm3). The water absorption and thickness swelling values observed in this study were higher for AA/epoxy composite, revealing its higher cellulosic content, compared to the other composite materials. The examination of fiber pull-out, matrix cracks, and fiber dislocations in the microstructure and fractured surface morphology of the developed materials confirmed the trends for mechanical properties. Overall, from results analysis it can be concluded that reinforcing epoxy matrix with AA filler effectively improves the properties of the developed composite materials. Thus, date palm fruit bunch stalk filler might be considered as a sustainable and green promising reinforcing material similarly to other natural fibers and can be used for diverse commercial, structural, and nonstructural applications requiring high mechanical resistance.